Pengaruh Teknik Pola Ci – Luk – Ba Terhadap Keterampilan Menulis Cerita Pendek Pada Siswa Kelas IV SDN Ketabang Surabaya - Sintia Dwi Agustin; Triman juniarso; Pana Pramulia (Universitas Mathla'ul Anwar Banten, 2020)
Language skills are a very important skill in everyday life. Language skills are easily expressed through oral and written. The lack of interest of students in terms of writing about his own experiences is happening because of difficulties to express feelings, not able to describe the idea in the form of sentences. Pattern Technique Ci-Luk-Ba! is a technique for writing a story that contains the most basic structure of the narrative. Therein, there is knowledge, tension and enjoyment, while making the story start from the starting point, middle, and end point. The purpose of this research is to know the influence of Ci-Luk-Ba pattern techniques! To short story writing skills. The method used by this research is quantitative using Quasi Experimental Design. Using sampling technique is Non probability Sampling with purposive sampling form. The results of data analysis showed significant differences proved also on the hypothesis test indicating that t_hitung gained 9.85 greater than t_tabel 1.994 at a significant rate of 0.05. It can then be concluded that rejected received. So it can be stated that